2013
DOI: 10.1371/journal.ppat.1003152
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Impairs Nucleotide Binding Oligomerization Domain (Nod1)-Mediated Innate Antibacterial Renal Defenses in Mice and Human Transplant Recipients

Abstract: Acute pyelonephritis (APN), which is mainly caused by uropathogenic Escherichia coli (UPEC), is the most common bacterial complication in renal transplant recipients receiving immunosuppressive treatment. However, it remains unclear how immunosuppressive drugs, such as the calcineurin inhibitor cyclosporine A (CsA), decrease renal resistance to UPEC. Here, we investigated the effects of CsA in host defense against UPEC in an experimental model of APN. We show that CsA-treated mice exhibit impaired production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 67 publications
1
59
0
Order By: Relevance
“…The susceptibility to fungal infection caused by CsA was also shown to be the consequence of an innate immune pathway regulating antifungal resistance in neutrophils (47). CsA can also impair nucleotide binding oligomerization domain 1 (Nod1)-mediated innate antibacterial renal defenses in mice and human transplant recipients, and these results confirmed that inhibition of Nod1-mediated innate immune response together with the decrease in Toll-like receptor 4 (TLR4)-mediated production of chemoattractant chemokines caused by CsA may contribute to sensitizing kidney grafts to acute pyelonephritis (48). However, the immune regulatory effect and important role in transplant immunology of calcineurin inhibitors is highly complex.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The susceptibility to fungal infection caused by CsA was also shown to be the consequence of an innate immune pathway regulating antifungal resistance in neutrophils (47). CsA can also impair nucleotide binding oligomerization domain 1 (Nod1)-mediated innate antibacterial renal defenses in mice and human transplant recipients, and these results confirmed that inhibition of Nod1-mediated innate immune response together with the decrease in Toll-like receptor 4 (TLR4)-mediated production of chemoattractant chemokines caused by CsA may contribute to sensitizing kidney grafts to acute pyelonephritis (48). However, the immune regulatory effect and important role in transplant immunology of calcineurin inhibitors is highly complex.…”
Section: Discussionmentioning
confidence: 77%
“…Although NFATs have been extensively studied in the context of T cells, relatively few studies have examined their function in myeloid lineages. However, several recent studies about calcineurin signaling in innate immune effects have showed their NFAT-dependent regulatory effects (45)(46)(47)(48). In the present study, we demonstrate the intrinsic regulatory effects of MDSCs in prolonging allograft survival and show a previously unknown feature of MDSC function in immunohomeostasis, i.e., the reprogramming of T cell differentiation from T H 1 to T H 2 and CD8 ϩ T cell differentiation, which represents a novel mechanism of calcineurin amelioration of transplant immunological rejection by targeting the NFAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is crucial for activation of inflammatory responses to Af and for recruitment of fungicidal neutrophils to the site of infection. Calcineurin-NFAT signaling has also been shown to be critical for the innate immune response to Candida albicans and Escherichia coli through endocytic mechanisms convergent on phospholipase C-g-dependent calcium flux (16,17). These observations underscore the importance of calcineurin-NFAT signaling for myeloid immunity, and they reveal a novel relationship between innate sensing and calcineurin-NFAT signaling in the lung that requires further clinical definition.…”
mentioning
confidence: 88%
“…Since we previously showed that CsA impairs Nod1 expression in renal tubular cells infected with UPEC [16], we checked that Let-7i had no effect on Nod1 expression (online suppl. Fig.…”
Section: Csa Induces Let-7i Expression Targeting Tlr4 In Renal Collecmentioning
confidence: 99%
“…Interestingly, CsA was also shown to impair cytokine-induced matrix-metalloproteinase-9 associated with an inhibition of the IL-1β-induced activation of the transcription factor NF-κB and mitogen-activated protein (MAP) kinase c-Jun N-terminal kinase (JNK) in rat mesangial cells [15]. Moreover, we previously showed that CsA impairs nucleotide binding oligomerisation domain (Nod1)-mediated innate antibacterial renal defenses in mice and human transplant recipients [16,17]. These findings raised the possibility that CsA can impair the activation of MCD cells caused by LPS and UPEC, and thereby favour the intrarenal colonisation of UPEC.…”
mentioning
confidence: 99%